Interannual variation of larval fish assemblages in the Gulf of Cádiz (SW Iberian Peninsula) in relation to summer oceanographic conditions - Mafalda Júnior,Paulo (2006)
Two ichthyoplankton surveys were conducted during July 1994 and July 1995 in the Gulf of Cádiz with the aim of describing composition, abundance, distribution patterns and interannual variations of larval fish assemblages. Interannual differences were found in this study. In 1994, higher salinities were observed at external sites, though in 1995, higher values were observed at intermediate sites. The upper water column was warmer in 1994 and had less fish larvae density. During 1994, Sardinella aurita and Engraulis encrasicolus were abundant but spatial location was opposite. In 1995, abundance of both species was very different, but with similar spatial pattern. Cluster analysis revealed well-defined groups of stations and assemblages of larvae, primarily related to bathymetry. The "inshore assemblage" occupied the shallow coast area; its characteristics species being closely related to the estuarine system, mainly comprising Engraulis encrasicolus and Gobiidae. The "shelf assemblage" occupied the continental shelf and its characteristics species consisted of larvae whose adults inhabited the shelf province and spawn in the same zone, like Sardinella aurita and Trachurus spp. Interannual variations in composition and extension of the subgroups could be attributed to the main circulation patterns, continental water discharge and spawning strategies of fishes.